2006
DOI: 10.1187/cbe.05-07-0089
|View full text |Cite
|
Sign up to set email alerts
|

From Organelle to Protein Gel: A 6-Wk Laboratory Project on Flagellar Proteins

Abstract: Research suggests that undergraduate students learn more from lab experiences that involve longer-term projects. We have developed a one-semester laboratory sequence aimed at sophomore-level undergraduates. In designing this curriculum, we focused on several educational objectives: 1) giving students a feel for the scientific research process, 2) introducing them to commonly used lab techniques, and 3) building skills in both data analysis and scientific writing. Over the course of the semester, students carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Other laboratory courses described in the literature have used varying strategies to generate interest and engagement with biochemistry course material [21,22]. We employed the ''hook'' of allowing the research laboratory course students to participate in the actual research enterprise by their generation of novel mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratory courses described in the literature have used varying strategies to generate interest and engagement with biochemistry course material [21,22]. We employed the ''hook'' of allowing the research laboratory course students to participate in the actual research enterprise by their generation of novel mutants.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown in other situations to enhance integrated and long-lasting student learning [21,23,24]. We did not use assessment tools that would allow us to make similar statements; however, what distinguishes this undergraduate laboratory course is that the experiments effectively intertwined basic research and a laboratory skills course to strengthen the research-teaching nexus.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the design of BIO106's YAC stability in mitosis research project was inspired by published work of Spencer et al (1990). Examples of other inquiry-based laboratory courses/ modules involving yeast (Odom and Grossel 2002;Vallen 2002;Gammie and Erdeniz 2004), bioinformatics and human disease (Bednarski et al 2005), apoptosis in cultured human cells (Dibartolomeis and Moné 2003), Chlamydomonas (Mitchell and Graziano 2006), and plants (Wenzel 2006) have been reported. In summary, the ''Research in Genetics'' course allowed students to experience scientific inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Students in four lab sections of Fundamentals of Genetics lab (LSC348, generally taken by sophomore-level students) were asked to complete pre-and postlab exercise surveys to determine students' self-assessment of knowledge and their evaluation of and interest in the exercise (Cunningham et al, 2006;Mitchell and Graziano, 2006). Students filled out the paper surveys anonymously, and all surveys were in no way linked to a student or lab section.…”
Section: Laboratory Exercise Evaluationmentioning
confidence: 99%
“…The report indicated that science laboratories should develop students' ability to think independently and expose students to actual scientific protocols and research methods. Additional research into improving science education established that multiweek project-based labs enhance student learning and demonstrate "doing science," because they mimic what actually happens in the research setting (Mitchell and Graziano, 2006). Inquiry-based laboratory activities have been demonstrated to be effective at piquing students' interest (e.g., Cunningham et al, 2006;Mitchell and Graziano, 2006) and enhancing their ability to design experiments and interpret data (Myers and Burgess, 2003;Howard and Miskowski, 2005).…”
Section: Introductionmentioning
confidence: 99%